Pengaruh Metode Ekstraksi Terhadap Karakteristik Kolagen dari Kulit Ikan Patin (Pangasius pangasius) - Nadia Fabella; Herpandi Herpandi; Indah Widiastuti (Universitas Sriwijaya, 2018)
The purpose of this research was to know difference pretreatment effect to characteristic of collagen from Stripped Catfish (Pangasius pangasius) Skin. This research was conducted on April until July 2017 using the Randomized Block Design with three treatments (method by Alhana et al., (2015), Baehaki et al., (2016) and Rahmayanti (2014) and repeated three times. The parameters observed in this research were yield of crude collagen, protein, and amino acid. The result showed that treatments gave significant effect on protein of collagen. But there were no effect on the yield of crude collagen and amino acid. The result of this study indicated that average yield values of stripped catfish skin collagen of sample A1, A2, dan A3 were 5.85%, 7.12%, and 6.35%. Protein content that collagen were 34.57%, 33.83%, and 50.11%. The highest amino acid of stripped catfish skin collagen were glisine and proline.